Pelatihan Pembuatan E-Modul dengan Flipbook bagi Guru-guru di SD Muhammadiyah 1 Kota Palangkaraya - Rita Rahmaniati; Siti Juhairiah; Doddy Teguh Yuwono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Training on Making E-Modules with Flipbooks for Teachers at SD Muhammadiyah 1 Palangkaraya City. The service activity carried out was training in making flipbook media for Teachers at SD Muhammadiyah 1 Palangkaraya. The partner of the service activities carried out is Teachers at SD Muhammadiyah 1 Palangkaraya. Based on the interviews with the Chief Principal and Secretary of Education and Culture, there has never been any training on learning media, especially flipbooks and as many as 85% of teachers have never used digital media in learning. Based on these problems, the service activities carried out offer comprehensive training starting from understanding media literacy, the importance of learning media, providing material on flipbook media, how to make flipbook media according to the steps described and how to use flipbook media in learning. Service activities are carried out in September-November 2021 with the online and offline methods. The output targets of service activities carried out are in the form of services and publications. The service output is in the form of material exposure through training on making flipbook media. The steps taken in this service activity are Exposure to material about media literacy, Exposure to material about learning media, Exposure to material about flipbook media, making flipbook media, Application of flipbook media. The publication output in the form of the result of making e-modules using flipbooks is simply online.